LEI DE PROPRIEDADE INDUSTRIAL: PARÁGRAFO ÚNICO DO ARTIGO 40 DA LEI 9.279/96 E ACESSO A MEDICAMENTOS GENÉRICOS (Revista Direito em Debate, 2019)
The research aims to analyze the effects of the application of the single paragraph from article 40 of the Industrial Property Law, which provides the possibility of extending the validity of the patent regarding the access to generic medicines. It presents a view about the protection of the intellectual property as a fundamental right. It also verifies the situation of the analysis of patent applications process, under the responsibility of the National Institute of Industrial Property (INPI), as a way of understanding what led the legislator to introduce the aforementioned paragraph in article 40 of the Industrial Property Law, especially regarding generic medicines. The method used is the deductive, based on legislation bibliographical revision, doctrine and jurisprudence. It is concluded that the single paragraph of the article 40 of the Industrial Property Law, which aimed to minimize the damages of inventors in the face of the delays in the processing of patent applications by INPI, which should only occur in exceptional cases, is systematically applied because of the backlog, delaying the entry of new generic medicines in the market and, consequently, preventing more people from accessing generic medicines, which are generally cheaper, safer and more effective than traditional medicines.
Keywords: Generic medicine; Patent; Industrial Property; Intellectual Property; Patent Extension.